2017
DOI: 10.5539/ijbm.v12n6p189
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leader-Member Exchange on Innovative Work Behavior in the Saudi Hospitality

Abstract: This study investigated whether a relationship exists between leader-Member exchange (LMX) and innovative work behavior (IWB) of hotel sector employees in the territory of Riyadh. LMX's overall effect on innovative employee work behavior can be seen in the values of R 2 = 0.655 and adjusted R 2 =0.423. Overall, the results explain 65 percent of the variation in innovative employee behavior, which represents a satisfactory and positive result for the study and supported the study's hypotheses. One aim of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
1
16
0
5
Order By: Relevance
“…Accordingly, leadership would involve followers beyond organizational boundaries (Moon, et al, 2018) (Janssen, 2005). Consequently, the individuals and employees have a positive situational sense to determine what is to be carried out (Rosile, et al, 2018) (Alsughayir, 2017) Now, especially with financial situations and competitiveness creativity and intrinsic motivation are crucial for organizational success. Employers must consider the importance of employee creativity and intrinsic motivation.…”
Section: Leadershipmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, leadership would involve followers beyond organizational boundaries (Moon, et al, 2018) (Janssen, 2005). Consequently, the individuals and employees have a positive situational sense to determine what is to be carried out (Rosile, et al, 2018) (Alsughayir, 2017) Now, especially with financial situations and competitiveness creativity and intrinsic motivation are crucial for organizational success. Employers must consider the importance of employee creativity and intrinsic motivation.…”
Section: Leadershipmentioning
confidence: 99%
“…Employers must consider the importance of employee creativity and intrinsic motivation. A leader should be having the ability to initiative decisions taking towards the development factors as well as can maintain the positive functioning relationships in the organization (Feng, et al, 2018), (Akram, et al, 2016), (Alsughayir, 2017). Hence, a leader has a major supportive role.…”
Section: Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Interpersonal relationships and relationships nurtured between employees and their immediate leaders should not be underestimated. Scholars have increasingly demonstrated that leader-member exchanges enhance trust, respect, support, and loyalty and also facilitate the acquisition of innovative work behavior (Alsughayir, 2017;Bibi & Afsar, 2018;Tastan & Davoudi, 2015). Despite several policies being developed to guide innovativeness in organizations in Kenya, investment in leader-member exchange remains silent in most of these policies.…”
Section: Introductionmentioning
confidence: 99%